Factors Affecting the Utilization of Hospital Management Information System in PKU Muhammadiyah Bantul General Hospital - Yeni Komalasari (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2020)
Hospitals are important institution in organizing health system in Indonesia. Because of its important role, it is crucial to ensure the data credibility. Therefore, protected by law, hospitals obliged to maintain their system information. This study conducted adopting Technology Acceptance Model (TAM) variable. This study was held in Bantul Regional General Hospital using cross sectional approach. Population of this study is all staff who are identified to be involved in the use of hospital management information system in PKU Muhammadiyah Bantul General Hospital as much as 325 staff. Sample were taken using proportionate stratified random sampling as much as 85 staff. Research data obtained by distributing questionnaires and analyzed using chi square and Mann Whitney test. Univariate analysis showed not good perceived benefit (58,8%), good perceived ease of use (52,9%) and not good attitude of using (69,4%). Bivariate analysis showed variables affecting utilization of hospitals management information system are perceived benefit (p=0,001), perceived ease of use (p=0,018) and attitude of using (p=0,021). Multivariate analysis showed the most affecting variables towards utilization of hospitals management information system are perceived benefit (p=0,008) and perceived of ease use (p=0,049).